اختيارات ابي عيسى الترمذي الفقهية من خلال تراجمه في كتاب الجامع - بوغزالة محمد, فاطمة (University of Eloued جامعة الوادي, 2017)
يتناول هذا البحث دراسة تراجم جامع الإمام الترمذي, وذلك من جانبين: أولا: جانب نظري؛ بينت فيه مفهوم التراجم؛ فعرفت بها لغة واصطلاحا, وذكرت أسسها, كما ذكرت أقسام التراجم عند الإمام الترمذي؛ فهي على ثلاثة أقسام: ظاهرة, واستنباطية, ومرسلة وذكرت فوائدها, وأهم المصادر التي اعتنت بدراستها, فوجدت أن كتاب البخاري "الصحيح", هو وحده من حظيت تراجمه بدراسات مستقلة, وقبل كل هذا قدمت بترجمة مختصرة للإمام الترمذي, وعرفت بكتابه الجامع. ثانيا: جانب تطبيقي؛ انتقيت فيه عددا من التراجم التي يظهر من خلالها اختيار الإمام الترمذي واضحا في أبواب فقهية معينة؛ فاخترت نماذج من فقه العبادات( الطهارة, والصلاة, والزكاة, والصوم, والحج), وكذلك نماذج من فقه المعاملات (البيوع, والأطعمة, والأسرة, والفرائض), وضَّحت من خلالها اختيار الإمام الترمذي الفقهي في هذه المسائل, مهدت لها بتصوير, وذلك بذكر أراء أهل العلم فيها, وذكرت اللفظ الدال على اختياره من الترجمة, مع توضيح ما يدعم اختياره من غير الترجمة, كأحاديث الباب مثلا, وكذلك من خلال تعليقه بعد ذكر تلك الأحاديث, مما أبان لي عن اختياره الفقهي في تلك التراجم This research deals with the studay of translations of jami' at-tirmidhi in two sides: First: theoretical side, it shows the concept of translations, its definitios of language and terminology, its foundations, also I mentioned the sections of the translations of the imam at-tirmidhi, they are in three sections: visible, deductive and consignor.I mentions its benefits and the most important sources those are considered by its study, I found that the book al-bukhari<>,it is the Alon had its translations with independent studies, before all this, I provided a brief translations to al-imam at-tirmidhi and I defined his book al-jami' Second, application side, I selected a mumber of translations which it appears the selection of al-Imam atirmidhi is clear in specific sections of jurisprudence, I chose exemples of the jurisprudence of worship (Purity, Prayer, Zakat, Fasting and Hajj). Also exemples of the jurispruidenc of transactions ( sales, food, family and the Obliations) I clarified through them the choice of jurisprudence of al-Imam at-tirmidhi in these issues, Imentioned the views of the Scholars and the word is chosen from the translation, With an explanation of What it supports its selection Without tuanslation as Ahadith of the section also by commenting after the mention of Ahadith Which explained to me his choise of jurisprudence in those translations
مذكرة ماستر تخصص علوم الحديث
Keywords: الاختيارات الفقهية – التراجم – الإمام الترمذي - الجامع; choise of jurisprudence - the book – al-Imam at-tirmidhi- book al-jami'